Markedly Increased High-Mobility Group Box 1 Protein in a Patient with Small-for-Size Syndrome - Darren G. Craig; Patricia Lee; E. Anne Pryde; Ernest Hidalgo; Peter C. Hayes; Stephen J. Wigmore; Stuart J. Forbes; Kenneth J. Simpson (Case Reports in Transplantation)
Background. Small-for-size syndrome (SFSS) occurs in the presence of insufficient liver mass to maintain normal function after liver transplantation. Murine mortality following 85% hepatectomy can be reduced by the use of soluble receptor for advanced glycation end products (sRAGE) to scavenge damage-associated molecular patterns and prevent their engagement with membrane-bound RAGE. Aims. To explore serum levels of sRAGE, high-mobility group box-1 (HMGB1) protein, and other soluble inflammatory mediators in a fatal case of SFSS. Methods. Serum levels of HMGB1, sRAGE, IL-18, and other inflammatory mediators were measured by ELISA in a case of SFSS, and the results were compared with 8 patients with paracetamol-induced acute liver failure (ALF) and 6 healthy controls (HC). Results. HMGB1 levels were markedly higher in the SFSS patient (92.1 ng/mL) compared with the ALF patients (median (IQR) 11.4 (3.7–14.8) ng/mL) and HC (1.42 (1.38–1.56) ng/mL). In contrast, sRAGE levels were lower in the SFSS patient (1.88 ng/mL) compared with the ALF patients (3.53 (2.66–12.37) ng/mL) and were similar to HC levels (1.40 (1.23–1.89) ng/mL). Conclusion. These results suggest an imbalance between pro- and anti-inflammatory innate immune pathways in SFSS. Modulation of the HMGB1-RAGE axis may represent a future therapeutic avenue in this condition.